2015
DOI: 10.1021/acs.molpharmaceut.5b00839
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of Nedd4-2 in the Ubiquitination, Expression, and Function of Organic Anion Transporter-3

Abstract: Organic anion transporter-3 (OAT3) is a member of the organic anion transporter family that mediates the body disposition of a diverse array of clinically important drugs. We previously demonstrated that activation of protein kinase C (PKC) inhibits OAT3 transport activity by accelerating OAT3 internalization from cell surface into intracellular compartments. In the current study, we established that PKC-induced inhibition of OAT3 transport activity in monkey kidney COS-7 cells and in human kidney HEK293 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
(91 reference statements)
3
21
0
Order By: Relevance
“…Our laboratory recently demonstrated (Xu et al, ; Xu et al, ) that Nedd4–2 directly binds to OATs and catalyses the attachment of ubiquitin molecules to these transporters, which leads to the endocytosis/internalization of OATs from the plasma membrane to intracellular endosomes and subsequent degradation. Consequently, the amount of OATs at the plasma membrane is reduced and their transport activity is decreased (Xu et al, ; Xu et al, ; and our unpublished results). In exploring the relationship among sgk1, Nedd4–2 and hOAT3, it was found that sgk1 phosphorylated Nedd4–2 (Figure ) weakened the interaction between Nedd4–2 and hOAT3 (Figure ) and decreased hOAT3 ubiquitination (Figure ).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Our laboratory recently demonstrated (Xu et al, ; Xu et al, ) that Nedd4–2 directly binds to OATs and catalyses the attachment of ubiquitin molecules to these transporters, which leads to the endocytosis/internalization of OATs from the plasma membrane to intracellular endosomes and subsequent degradation. Consequently, the amount of OATs at the plasma membrane is reduced and their transport activity is decreased (Xu et al, ; Xu et al, ; and our unpublished results). In exploring the relationship among sgk1, Nedd4–2 and hOAT3, it was found that sgk1 phosphorylated Nedd4–2 (Figure ) weakened the interaction between Nedd4–2 and hOAT3 (Figure ) and decreased hOAT3 ubiquitination (Figure ).…”
Section: Discussionsupporting
confidence: 75%
“…Our laboratory recently demonstrated (Xu et al, ; Xu et al, ) that Nedd4–2, a ubiquitin ligase, binds to OAT and inhibits OAT transport activity by promoting the conjugation of ubiquitin to OAT, which leads to OAT internalization from the plasma membrane and subsequent degradation (Xu et al, ; Xu et al, ; and our unpublished results). This experiment examined the relationship among sgk1, Nedd4–2 and hOAT3 using a co‐immunoprecipitation strategy.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations